Review FotoForensic.com dengan Teknik Eror Level Analysis dan JPEG untuk mengetahui Citra Asli - Fajar Mahardika; Aurora Dwi Khatulistian; Adam Prayogo Kuncoro (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
In this modern era of photography, many facilities including software or hardware can be used as a tool to produce better images and so on falsified images. This research aimed to simulate falsified image detection, utilizing developed error level analysis method. The output of this research is a decision whether an image is authentic one or falsified one. From the testing phase, it can be concluded that the developed method error level analysis method resulted a good detection accuracy.